2012
DOI: 10.1130/ges00849.1
|View full text |Cite
|
Sign up to set email alerts
|

Identifying origins of and pathways for spring waters in a semiarid basin using He, Sr, and C isotopes: Cuatrocienegas Basin, Mexico

Abstract: He, C, and Sr isotopes are used to infer spring sources in a water-stressed area. Spring-water origins and pathways in the Cuatrociénegas Basin are revealed by linking structure and geochemistry via regionally extensive fault networks. This study presents the fi rst dissolved noble gas and He isotopic data from northeastern Mexico. Basementinvolved faults with complex reactivation histories are important in northeastern Mexico tectonics and affect hydrogeologic systems. The importance of faults as conduits for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 43 publications
0
43
1
Order By: Relevance
“…Waters issuing from the western springline ( Fig. 2) and high discharge springs in the CCB support the wetland ecosystem located around the piedmont of the Sierra San Marcos, and are the same as those used to irrigate farms in the region (Wolaver et al 2013). Thus, areas W(a) and (b) were of particular importance due to their proximity to the western springline of the Sampling sub-region (Fig.…”
Section: *Figure 2* 2 Methodsmentioning
confidence: 91%
See 3 more Smart Citations
“…Waters issuing from the western springline ( Fig. 2) and high discharge springs in the CCB support the wetland ecosystem located around the piedmont of the Sierra San Marcos, and are the same as those used to irrigate farms in the region (Wolaver et al 2013). Thus, areas W(a) and (b) were of particular importance due to their proximity to the western springline of the Sampling sub-region (Fig.…”
Section: *Figure 2* 2 Methodsmentioning
confidence: 91%
“…Recharge elevation has been suggested as a reason for these differences (Johannesson et al 2004;Rodriguez et al 2005) with estimates in the region of -0.48‰/100 m for δ 18 O (Rodriguez et al 2005). However, residence times >60 yr (Wolaver et al 2013) and the well mixed nature of the CCB groundwater indicated by adherence to the LEL (Fig. 3a) suggests that recharge elevation estimates may be inaccurate (Blasch and Bryson, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Groundwater lags have been shown to have long residence times of decades to centuries (Rodríguez et al, 2005;Wolaver et al, 2013) In the Southwest, winter and spring precipitation is enhanced during El Niño events (Heyer et al, 2017). Scanlon et al (2006) indicated that periods of frequent El Niño events result in three times as much groundwater recharge in the desert Southwest as compared to periods of frequent La Niña events.…”
Section: Discussionmentioning
confidence: 99%